"Bagels and doughnuts … round food for every mood" food advertising discourses. Issue 2 (1st February 2016) - Maddock, Sarah; Hill, Beverley
Abstract : Purpose: – The relationship between food and mood has been discussed for many years. The purpose of this paper is to extend that debate by exploring how food advertising, a key source of consumer information about food, utilises and implies varied associations between food and mood. Design/methodology/approach: – The research combines a textually oriented analysis with an analysis of the visual images in a sample of typical food advertisements drawn from women's magazines. Findings: – Although healthy foods have the potential to enhance mood this is not often used as a key advertising message. Conversely, advertisements for foods that can depress mood frequently adopt messages of happiness and wellbeing. Research limitations/implications: – This exploratory research provides an initial investigation of advertising discourses of food and mood at a snapshot in time. Based on the findings derived from this limited sample, further research is suggested which would provide a more comprehensive survey of food advertising. Practical implications: – The research is of value to food promoters in suggesting that they review food messages and the use of emotional appeals in the light of developing scientific research on the link between food and mental wellbeing. Social implications: – The growing interest in promoting mental health and wellbeing means that consumers and governments are keen to understand the relationship between food and mood and its potential influence on consumer food choices. Originality/value: – This research indicates that some food advertising diverges from the scientific evidence on food and mental health and wellbeing. The research is therefore of value to food promoters and advertising regulators.